The role of artificial intelligence in protecting frontline forces in CBRNE incidents - Hesam Seyedin; Shandiz Moslehi; Asghar Tavan; Sajjad Narimani (Progress in Disaster Science)
Chemical, Biological, Radiological, Nuclear, and Explosive (CBRNE) incidents present unprecedented challenges to frontline forces, including emergency responders, military personnel, and healthcare workers. These individuals face not only physical dangers but also significant cognitive, behavioral, and psychosocial stressors that can compromise their performance and well-being. Artificial Intelligence (AI) has emerged as a transformative tool in enhancing the safety, effectiveness, and resilience of frontline forces in such high-stress environments. This paper explores the multifaceted role of AI in safeguarding frontline personnel, focusing on its applications in cognitive support, behavioral monitoring, psychosocial well-being, and training.